Impact of gravel bar flooding on arthropods in the upper Isar: implications for river management - R. Wessels; A. Sundermann; A. Sundermann; A. Sundermann (Web Ecology)
Braided rivers are dynamic ecosystems with constantly shifting flow patterns that create diverse habitats, supporting species highly adapted to frequent flooding and gravel relocation. Arthropods inhabiting these areas use various strategies to survive floods, including migration, hiding, and physiological adaptations like flying or surviving submerged. This study aims to assess whether certain riverbank areas act as refuges during floods and to determine if dominant arthropod species actively or passively respond to rising water levels, with implications for the conservation of these ecosystems. This study focused on the spatial distribution and flood response of two spider species and two beetle species in a gravel bank area along the upper Isar (Germany). Species distributions were recorded under normal conditions and compared to their distribution after a flood event, using 203 sampling squares. In addition, an artificial flood experiment was conducted to observe species behaviour under rising water. Flooding significantly altered the distribution of the studied species, with many individuals relocating to higher areas like slopes during peak flood and scattering across the exposed gravel bar once waters receded. In an artificial flood experiment, individuals initially took refuge in gravel but eventually crossed the water's surface to escape rising water levels, showing varied survival behaviours like floating on stones or paddling to safety. The study highlights the critical role of accessible elevated areas and riverbanks as refuges for arthropods during flooding, with 39 % of individuals actively utilizing these sites in response to rising water levels. The findings emphasize that riverbanks and elevated areas must be preserved and managed effectively, as they provide vital refuge conditions for arthropod communities, ultimately fostering ecological resilience in natural river systems.